The Reference of architectural Identity of Kurdistan Region of Iraq - Aloomary, Rana Fathi; Aloomary, Rana Fathi (Sulaimani Journal for Engineering Sciences, 2014)
contemporary communities since nothing more than identity satisfies the individual's quest to achieve his global existence through his belonging to a large unit that embraces him. Since architecture is the civilized expressive outcome of community's ideology, identity has been the subject for many studies and research, and has been studied and researched by many philosophers and critics from different perspectives. Since the concept of identity tackles different knowledge fields, it has added a diverse impression on our contemporary architecture in general and in Kurdistan in specific and is characterized by constant change impacted by technical, economical, political and social factors. The exposure of Kurdistan to the effect of economic expansion and the development of technology, mass media, and communication had an effect on the existence of an architectural style characterized by rapid change. This caused first governing the architectural shape resulted from frequent ideology and the different expressions of considerations to our environment (and this is through the international modern trend). The governing of west civilization increased in all domains architecture being one of them to the extent that it controlled the privacy of architecture. From this point, the research came to show the architectural identity in Kurdistan Region.